2007
DOI: 10.1111/j.1468-1293.2007.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of metabolic drugs and fish oil in HIV‐positive patients with metabolic complications and associations with dyslipidaemia and treatment targets

Abstract: BackgroundHighly active antiretroviral therapy (HAART) with protease inhibitors (PI) is successful in suppressing viral replication, but may lead to a range of metabolic abnormalities associated with cardiovascular disease (CVD). ObjectivesThe first objective of the study was to compare baseline demographic and clinical characteristics between PI users and non-PI users referred to a specialized metabolic clinic during [1999][2000][2001][2002][2003]. The second objective was to assess the associations of prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In the D:A:D study, at the time of any cardiovascular event, only 23% were receiving lipid-lowering medication and a further 45% were treated in the following 6 months. 93 Even when lipid-lowering drugs are used, more than 50% do not reach the levels recommended by the ATP-III guidelines in two cohort studies 94,95 and one randomised trial. 96 The management of hypertension and diet are components of the management and prevention of dyslipidaemia and CVD.…”
Section: Preventionmentioning
confidence: 99%
“…In the D:A:D study, at the time of any cardiovascular event, only 23% were receiving lipid-lowering medication and a further 45% were treated in the following 6 months. 93 Even when lipid-lowering drugs are used, more than 50% do not reach the levels recommended by the ATP-III guidelines in two cohort studies 94,95 and one randomised trial. 96 The management of hypertension and diet are components of the management and prevention of dyslipidaemia and CVD.…”
Section: Preventionmentioning
confidence: 99%
“…Another important concern is that the effects of lipidlowering treatment in HIV-infected patients appear to be relatively modest, with more than 50% of patients not reaching ATP-III goals in two retrospective cohort studies [20,21 ] and one randomized clinical trial [22]. A recent large observational study [23] showed a lower response to lipid-lowering therapy in HIV-infected than in non-HIV dyslipidemic subjects.…”
Section: Lipid-lowering Therapy In Hiv-infected Patientsmentioning
confidence: 99%
“…This demonstrates an enthusiasm and acceptance of these dietary supplements by HIV-positive adults with hypertriacylglycerolaemia. The effects of n-3 LC-PUFA on lipoprotein concentrations in HIV-positive adults are unclear, with no effect (262) , 11 % raised HDL (266) and 22·4 % raised LDL (258) reported. EPA and DHA have been shown to have anti-inflammatory effects in vitro via their role as PPAR-g ligands (267) and modulation of the NF-kB signalling system (268,269) .…”
Section: Interventionmentioning
confidence: 99%
“…The TAG-lowering effects of the n-3 LC-PUFA among HIV-positive adults are supported by three smaller prospective studies (262 -264) , although Virgili et al (265) showed no significant effect among nine HIV-positive subjects receiving 1120 mg EPA and 720 mg DHA daily for 6 weeks. A review of 237 hospital charts from HIV-positive adults with hypertriacylglycerolaemia showed that the use of n-3 LC-PUFA supplements was associated with a 32 % reduction in TAG concentrations (266) . Furthermore, at baseline 11 % of subjects used these dietary supplements, whereas at 6 months 25 % of subjects used the supplements (266) .…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation